2015
DOI: 10.1097/fjc.0000000000000248
|View full text |Cite
|
Sign up to set email alerts
|

20-Hydroxyeicosatetraenoic Acid Is a Key Mediator of Angiotensin II–induced Apoptosis in Cardiac Myocytes

Abstract: Cardiomyocyte apoptosis is involved in a variety of cardiac stresses, including ischemia-reperfusion injury, heart failure, and cardiomyopathy. Both Angiotensin II (Ang II) and 20-hydroxyeicosatetraenoic acid (20-HETE) induce apoptosis in cardiomyocytes. Here, we examined the relationship between 20-HETE and Ang II in cardiomyocyte apoptosis. Apoptosis was examined using flow cytometry in primary cultured rat cardiomyocytes treated with control, Ang II, and Ang II plus HET0016 (a 20-HETE formation inhibitor). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
2
14
1
Order By: Relevance
“…Likewise, Inhibition of ω-hydroxylase by DDMS reduced apoptosis in infarcted rat hearts in vivo (Wei et al, 2016), and HET0016 reduced apoptosis in Lanfgendorff-perfused hearts (Han et al, 2013). Ang-II-induced and ROS-mediated mitochondria-dependent apoptosis was attenuated by 20-HETE inhibition (HET0016) (Zhao et al, 2015), suggesting that like in vascular cells, 20-HETE mediates some of the detrimental effects of Ang II in cardiac myocytes. It is however unclear how assessment of apoptosis relates to MI size or post-MI remodeling since necrosis has been established as the predominant mode of myocyte cell death during MI.…”
Section: -Hete Function In the Heartmentioning
confidence: 99%
“…Likewise, Inhibition of ω-hydroxylase by DDMS reduced apoptosis in infarcted rat hearts in vivo (Wei et al, 2016), and HET0016 reduced apoptosis in Lanfgendorff-perfused hearts (Han et al, 2013). Ang-II-induced and ROS-mediated mitochondria-dependent apoptosis was attenuated by 20-HETE inhibition (HET0016) (Zhao et al, 2015), suggesting that like in vascular cells, 20-HETE mediates some of the detrimental effects of Ang II in cardiac myocytes. It is however unclear how assessment of apoptosis relates to MI size or post-MI remodeling since necrosis has been established as the predominant mode of myocyte cell death during MI.…”
Section: -Hete Function In the Heartmentioning
confidence: 99%
“…These specific experiments do have limitations, however, as ANG II treatment alone of H9c2 cardiac myocytes did not increase caspase-3 cleavage versus vehicle control treatment (data not shown). Although ANG II induces apoptosis of numerous cell types, including neonatal rat cardiac myocytes and vascular smooth muscle cells (26,38), it is possible that differentiated H9c2 cardiac myocytes are more resistant to ANG II, but cellular toxicity is unmasked in the presence of increased FoxO1 activity. Nevertheless, our observations are of interest, since cardiac-specific Foxo1-deficient mice are protected against diabetic cardiomyopathy, and Battiprolu et al (1) concluded that a reduction in Pdk4 expression and subsequent increase in glucose metabolism may be partly responsible for the observed benefit.…”
Section: H487mentioning
confidence: 99%
“…It remains to be determined whether 20-HETE activates PKC via a receptor or directly interacts with PKC similar to the action of DAG (366). More recently, 20-HETE-mediated mitochondrial ROS production was implicated in ANG II-induced apoptosis of neonatal rat cardiac myocytes (367). Enhanced apoptosis of cardiac myocytes by 20-HETE (353) may have significance for the etiology of heart failure, which is associated with increased apoptosis of cardiac myocytes, as well as other forms of cell death.…”
Section: Role Of 20-hete In Renal and Cardiac Ischemia Reperfusionmentioning
confidence: 99%